2013
DOI: 10.1002/app.39297
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the amorphous fraction of PEEK during annealing at atmospheric and high pressure above the glass transition temperature

Abstract: The constrained fraction of the amorphous phase of semi-crystalline polymers is in an out-of-equilibrium state so that "physical aging"-like features can be observed (e.g., by calorimetry) even above the glass transition temperature. This was already addressed in the literature in several semi-crystalline polymers at atmospheric pressure. Despite the well-known influence of pressure on molecular mobility, the pressure-sensitivity of these microstructure rearrangements has never been tackled. This study focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(95 reference statements)
4
6
0
Order By: Relevance
“…degree of supercooling. This observation is also reported by other authors [9,22], with an increase in the first endothermic peak, which occurs 10°C above the annealing temperature attributed to the melting of the secondary crystallization. In fact, for high annealing temperatures, the diffusion process is very important, with a high mobility of chains allowing the crystalline phase to be enhanced.…”
Section: Hillier Parameter Modelingsupporting
confidence: 90%
“…degree of supercooling. This observation is also reported by other authors [9,22], with an increase in the first endothermic peak, which occurs 10°C above the annealing temperature attributed to the melting of the secondary crystallization. In fact, for high annealing temperatures, the diffusion process is very important, with a high mobility of chains allowing the crystalline phase to be enhanced.…”
Section: Hillier Parameter Modelingsupporting
confidence: 90%
“…The doublemelting behaviour was previously reported for PEEK [34][35][36] and for PEKK by Quiroga Cortes et al [21]. No influence of the annealing temperature was observed on the value of melting peak, indicating that primary crystalline phase is not sensitive to the annealing process [16,37]. The annealing endotherm indicates the melting of secondary crystalline phase.…”
Section: Annealed Paek Lmsupporting
confidence: 69%
“…The annealing endotherm indicates the melting of secondary crystalline phase. Their origin could be ascribed to the reorganization of amorphous phase in smaller crystallites rather than to the primary crystalline phase [37].…”
Section: Annealed Paek Lmmentioning
confidence: 99%
“…We observed that w 1 is closed to 1 for low temperatures and then decreases to values lower than 0.5 for temperatures above 260 C. This shows that the formation of the secondary crystallization is promoted for low degree of supercooling. This observation has also been reported by few authors [18,39] with the increase of a first endothermic peak which occurs 10 C above the annealing temperature attributed to the melting of the secondary crystallization. In fact, for high annealing temperatures, the diffusion process is very important with a high mobility of the chains allowing the enhancement of the crystalline phase by the growth of a second crystalline structure within lamellae.…”
Section: Isothermal Crystallization Kinetic Modelingsupporting
confidence: 66%